Um estudo sobre intra-empreendedorismo e dimensão cultural em um grupo de trabalhadores de uma empresa cearense - Estevam, Artilene Barros Rabelo (2008)
This is a study about intrapreneuring practices and the cultural dimension “hierarchical distance” in Hofstede in a group of workers from a local company placed in the metropolitan area of Fortaleza. The aim of the research is to describe the main intrapreneuring practices hereby identified and their relationship with the cultural dimension aspects and hierarchical distance in the researched company. The methodology used was qualitative and descriptive according to case study. We adopted as an instrument of data collection the structured interview that is based on the conceptual basis of intrapreneuring and the cultural dimension “hierarchical distance” in Hofstede, Nine collaborators of the researched company were interviewed with the objective of describing the intrapreneuring practices in the researched company; relate intrapreneuring practices with the high direction behavior; relate the collaborators’ commitment with intrapreneuring practices; identify the style of the predominant leadership in the researched company and identify the level of hierarchical distance in the company. For the data treatment we used the content analysis method, Badin’s methodological reference (2004), which establishes information treatment and frequency of messages. It was observed that there are intrapreneuring practices in the researched company and that such practices are encouraged by the high direction. There is a relationship between the collaborators’ compromise and the intrapreneuring practices. However, it was not possible to identify the relationship between autonomy and intrapreneuring practice and it was confirmed that there is a relationship between the hierarchical distance and such practices. It was so concluded that through the intrapreneuring practices the organizations will be more prepared to the innovation and to face the challenges of the market. The cultural dimension “hierarchical distance” plays a very important role in the manifestation of those practices referred to in this study as primordial to the development of competitive advantage and the survival of organizations.